2018
DOI: 10.15252/embj.201798163
|View full text |Cite
|
Sign up to set email alerts
|

In vivo expansion of functionally integrated GABA ergic interneurons by targeted increase in neural progenitors

Abstract: A central hypothesis for brain evolution is that it might occur via expansion of progenitor cells and subsequent lineage‐dependent formation of neural circuits. Here, we report in vivo amplification and functional integration of lineage‐specific circuitry in Drosophila. Levels of the cell fate determinant Prospero were attenuated in specific brain lineages within a range that expanded not only progenitors but also neuronal progeny, without tumor formation. Resulting supernumerary neural stem cells underwent no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 63 publications
(100 reference statements)
1
27
0
Order By: Relevance
“…To identify the adult brain structures and associated functional modalities that derive from the embryonic DTB, we utilized genetic tracing of neural lineages employing the tracer line UAS-mCD8::GFP, tub-FRT-CD2-FRT-Gal4, UAS-FLP/CyO GMR Dfd YFP (39,40). We first deployed en-Gal4 as driver, which, combined with the tracer line, causes permanent GFP labeling of progeny of engrailed-expressing cells, even when those progeny themselves no longer express engrailed.…”
Section: Resultsmentioning
confidence: 99%
“…To identify the adult brain structures and associated functional modalities that derive from the embryonic DTB, we utilized genetic tracing of neural lineages employing the tracer line UAS-mCD8::GFP, tub-FRT-CD2-FRT-Gal4, UAS-FLP/CyO GMR Dfd YFP (39,40). We first deployed en-Gal4 as driver, which, combined with the tracer line, causes permanent GFP labeling of progeny of engrailed-expressing cells, even when those progeny themselves no longer express engrailed.…”
Section: Resultsmentioning
confidence: 99%
“…To identify the adult brain structures and functional modalities that arise from the embryonic DTB, we used genetic tracing of neural lineages (38,39). We traced engrailed expressing lineages of the embryonic neuroectodermal DTB (SI Appendix Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Mechanical stimuli trains consisted of 5 pulses of 200ms each, spaced by 800ms. Motor behaviour parameters were determined as previously described (38,75,76).…”
Section: In Situ Hybridization Immunocytochemistry and Imagementioning
confidence: 99%
“…But very few attempts have been there to link the two aspects (Tejedor et al , ; de Belle and Heisenberg, ; Walcourt and Nash, ; Hong et al , ; Blumröder et al , ). Shaw et al () have studied the effect of induced increase in progenitors and neuronal numbers in EB by attenuation of Prospero function. They have shown that the supernumerary neurons could form functional connections and could generate normal physiological and motor responses.…”
Section: Discussionmentioning
confidence: 99%